Muslim Consumer Behavior Analysis at Halal Product In Indonesia - Aziz Siregar, Fatahuddin; Hasibuan, Abdul Nasser; Monitorir Napitupulu, Rodame (KnE Social Sciences, 2023)
Indonesia with the majority of muslim population in the world should be able to be the center of halal industry in the world. Halal industry has a great potential to increase GDP in Indonesia. That is why muslim consumers themselves should be part of contributing to the halal industry. Basically, there are 8 sectors studied : food sector, finance sector, travel sector, clothing sector, media / recreation sector, pharmaceutical sector, cosmetics sector and medical care sector. In fact, the awareness of muslim society in Indonesia on halal product is still relatively low. That is why this study is important to conduct. This study used descriptive qualitative approach, with unrestricted sample where respondents can fill out questionnaires online during the period of questionnaire distribution with unlimited number of respondents. Of the 150 respondents who filled the questionnaires, only 136 who filled in completely, while the other 14 were incomplete so they were not used. Based on the analysis result, it is known that in the 8 sectors studied, there are external factors that influence the decision to purchase or use halal products, they are : demography, subculture, social class, values, family life cycle, and culture. While the internal factors influenced the decision to purchase or use halal products are : emotion, memory (in food and beverage sector); motive, emotion, and personality (in travel sector); motive, personality, emotion, and memory (in financial sector, clothing sector, cosmetic sector, and medical care sector). Meanwhile, all respondents stated that the decision to purchase or use halal products for 8 sectors were based on the needs and ease of finding them around the respondents. Keywords: Halal product; halal industry; Muslim consumer